Effect of Pb dopant On A.C mechanism of ZnS thin films - Shaban, Salma M. (Iraqi Journal of Physics, 2019)
Vacuum evaporation technique was used to prepare pure and doped ZnS:Pb thin films at10% atomic weight of Pb element onto glass substrates at room temperature for 200 nm thickness. Effect of doping on a.c electrical properties such as, a.c conductivity, real, and imaginary parts of dielectric constant within frequency range (10 KHz - 10 MHz) are measured. The frequency dependence of a.c conductivity is matched with correlated barrier hoping especially at higher frequency. Effect of doping on behavior of a.c mechanism within temperature range 298-473 K was studied.